2011
DOI: 10.5047/eps.2011.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Temperature correction and usefulness of ocean bottom pressure data from cabled seafloor observatories around Japan for analyses of tsunamis, ocean tides, and low-frequency geophysical phenomena

Abstract: Ocean bottom pressure (OBP) data obtained by cabled seafloor observatories deployed around Japan, are known to be significantly affected by temperature changes. This paper examines the relationship between the OBP and temperature records of six OBP gauges in terms of a regression coefficient and lag at a wide range of frequencies. No significant temperature dependency is recognized in secular variations, while substantial increases, at rates of the order of 1 hPa/year, are commonly evident in the OBP records. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 59 publications
5
9
0
Order By: Relevance
“…In this study, we assumed that the instrumental drift was linear, based on the conclusion of Inazu and Hino (). This assumption is reasonable at PG2 for the following two reasons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we assumed that the instrumental drift was linear, based on the conclusion of Inazu and Hino (). This assumption is reasonable at PG2 for the following two reasons.…”
Section: Resultsmentioning
confidence: 99%
“…For the seafloor pressure instruments, instrumental drift must be included in the estimated linear term and the pressure change due to tectonic movement. Because Inazu and Hino () showed that the annual mean pressure values of these two stations from 2000 to 2002 are almost linear within their standard deviations, we assumed that the instrumental drift could be modeled as a linear term. The estimated preseismic vertical velocity was −30 and −8.4 mm/yr for PG1 and PG2, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There seems no apparent coseismic offset for the foreshock in the corrected OBP records. Even in the corrected records, it was difficult to detect the postseismic displacement, as indicated by Inazu and Hino [2012]. Thus we assume the zero displacement at TM1 and TM2 for the co‐ and postseismic displacement in this study.…”
Section: Onshore and Offshore Geodetic Datamentioning
confidence: 99%
“…See Text S1 in the for more detailed description of the above analysis of the OBP data. The OBP data from the seafloor cabled system needs an additional temperature compensation [ Inazu and Hino , 2012] to detect vertical seafloor displacements (). There seems no apparent coseismic offset for the foreshock in the corrected OBP records.…”
Section: Onshore and Offshore Geodetic Datamentioning
confidence: 99%
“…7, in the future we have to enhance the sampling of the differential data from daily to higher than 1 Hz to detect the temporal and local leveling change due to shallower VLF swarms. In the hydraulic pressure gauges of DONET, water temperature gauges are also installed, which helps us to reduce the noise component in both the stack and differential data by temperature correction (Inazu and Hino 2011).…”
Section: Detectability Of Shallower Slow Earthquakes By Donetmentioning
confidence: 99%